TRANSFORMATION OF PAYMENT METHODS AMONG MILLENIALS: A STUDY ON THE ADOPTION AND EFFECTIVENESS OF ELECTRONIC MONEY IN PAREPARE CITY - Ramadhan, Fitrah Anugrah; Nur, Sri Wahyuni; Damirah; Addury, Multazam Mansyur (Islamic Financial And Accounting Review, 2025)
The digital revolution has changed the landscape of the payment system in Indonesia, especially among millennials who are increasingly adopting electronic money as the primary method of transactions. This study aims to analyze the adoption of factors that affect the use, as well as the effectiveness of electronic money in meeting the transaction needs of the millennial generation in Parepare City. Using a qualitative approach with a case study method, this study collected data through in-depth interviews with electronic money users from various social and economic backgrounds. The results of the study show that ease of use, transaction security, various incentives such as cashback and discounts, and social factors are the main factors in the adoption of electronic money. In addition, the effectiveness of electronic money can be seen in transaction efficiency, transaction automation, Accessibility and Flexibility, and Multitransactions. However, challenges such as uneven digital literacy and growing payment infrastructure are obstacles to wider adoption. These findings provide insights for financial service providers, governments, and the public in improving a more inclusive and effective digital payments ecosystem.